The Development of Android-Based Mobile-learning Media on Virus Material to Improve Learning Outcomes in Class X Senior High School - Desi Rahmasuci; Sri Ngabekti (FMIPA UNNES, 2023)
The purpose of this study was to test the feasibility, practicality, and effectiveness of learning media using Android-based mobile learning media on virus material to improve student learning outcomes. This type of research is